Who bears the cost of the business cycle? Labor-market institutions and volatility of the youth unemployment rate - Daiji Kawaguchi; Tetsushi Murao (IZA Journal of Labor Policy, 2012)
The way age-specific unemployment rates fluctuate over the business cycle differs significantly across countries. This paper examines the effect of labor-market institutions on the fluctuations of age-specific unemployment rates based on panel data of 18 OECD countries between 1971 and 2008. Empirical results suggest that the cost of the business cycle disproportionately falls on youths in countries with stricter employment protection. This implies that a higher adjustment cost of an existing workforce induces the employment adjustment of new entrants into the labor market.
Keywords: E24; J80; 330; unemployment; labor market institutions; business cycle; OECD; Konjunkturelle Arbeitslosigkeit; Junge Arbeitskräfte; Arbeitslosenversicherung; Gewerkschaftsmitgliedschaft; Arbeitsmarkt; Systemvergleich; OECD-Staaten